2006
DOI: 10.5005/jcdp-7-2-26
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Total-Etch Dentin Adhesive Systems on Peripheral and Central Dentinal Tissue: A Microtensile Bond Strength Test

Abstract: Objective The purpose of this study was to evaluate the microtensile bond strength (μ TBS) of four total-etch adhesives [Excite (EB), Prime & Bond NT (PBNT), Single Bond (SB), and One Coat Bond (OCB)] by comparing them to five self-etching adhesives (Clearfil SE Bond (CSEB), Xeno III (X III), Prompt L-Pop (PLP), AQ Bond (AQB), and Tyrian/One Step plus (TOSP)] at different dentinal areas. In addition the interface between the adhesive resins and dentin was examined using scanning electron microscopy (SEM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
7

Year Published

2008
2008
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
1
32
1
7
Order By: Relevance
“…Modern adhesive systems can be grouped according to their etching technique into two categories: total-etch (etch and rinse) and self-etch products (Yesilyurt and Bulucu, 2006). The first category utilizes the total-etch technique, which relies on the removal of the smear layer and exposure of the collagen matrix by acid etching, followed by the application of a self-priming agent that combines the primer and the adhesive resin into one solution (Proença et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern adhesive systems can be grouped according to their etching technique into two categories: total-etch (etch and rinse) and self-etch products (Yesilyurt and Bulucu, 2006). The first category utilizes the total-etch technique, which relies on the removal of the smear layer and exposure of the collagen matrix by acid etching, followed by the application of a self-priming agent that combines the primer and the adhesive resin into one solution (Proença et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hotta et al (1998) demonstrated that bonding agent polymerization is beneficial for strong adhesion between the tooth substance and restorative resins. Bond strength measurement is one of the most effective methods for characterizing commercial dentin bonding products (Yesilyurt and Bulucu, 2006). Bond strengths are generally tested in tension or in shear (Ozer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Furthermore a durable interfacial adhesion between tooth and biomaterial is essential for an ideal restoration. 21 As a part of aesthetic treatment, sometimes vital bleaching combines with aesthetic restorative procedures. When resin composite materials are used, the treatment of the enamel prior to adhesive restorative procedure is an extremely important step to achieve adequate retention of the composite material.…”
Section: Introductionmentioning
confidence: 99%
“…The type of adhesive system used is of the greatest importance for the quality of bonding (10,11). The use of self-etching primers in combination with resin-luting agents has been proposed for the cementation of endodontic posts to eliminate problems associated with the wet bonding technique (12,13).…”
mentioning
confidence: 99%